Decline in Respiratory Functions in Hospitalized SARS-CoV-2 Infected Cancer Patients Following Cytotoxic Chemotherapy—An Additional Risk for Post-chemotherapy Complications - Al-Mozaini, Maha Ahmed; Islam, Mihyar; Noman, Abu Shadat M.; Karim, ATM Rezaul; Farhat, Walid A.; Yeger, Herman; Islam, Syed S. (Frontiers in Medicine, 2022)
Background: Patients recovering from severe SARS-CoV-2 infection demonstrate impaired lung function and those requiring chemotherapy after recovering from SARS-CoV-2 infection have yet to be explored. In this study, we sought to investigate the possible pulmonary functional changes after administering chemotherapy in patients with prior SARS-CoV-2 infection. Methods In this study, a total of 37 cancer patients recovered from severe SARS-CoV-2 who received subsequent cytotoxic chemotherapy, were enrolled and prospectively followed-up. The following parameters were prospectively measured before (P1), after first chemotherapy cycle (P2), and 10 weeks after the end of chemotherapy (P3), to assess their impact on respiratory complications in terms DLCO, FEV1, FVC, 6MWT and levels of key inflammatory markers. Results: All patients completed at least 2 cycles of chemotherapy without showing overt respiratory complications. Six patients (16%) complained about dyspnea during chemotherapy or at follow-up period. DLCO was significantly impaired during follow-up period (from P1 78% to P3 60% of predicted values; IQR 55-89) and in 32 of 37 (86% of patients) from P1 to P2 (65% of predictive value; IQR 58-70; p<0.001). Four (11%) patients experienced post-chemotherapy respiratory complications. As expected, all patients from control groups showed improved pulmonary functions. Conclusions The risk of respiratory complications due to cytotoxic chemotherapy in prior SARS-CoV-2 infected patients is linked to loss of DLCO. Accordingly, we recommend that for cancer patients requiring chemotherapy after recovering from prior SARS-CoV-2 infection, pulmonary tests to be performed routinely before and during chemotherapy treatment to monitor the pulmonary performance.